2002
DOI: 10.1159/000064018
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Computed Tomography Findings Are Correlated with Disease Severity in Asthma

Abstract: Background: The structural changes in the airways of asthmatics are also referred to as remodeling and can be identified using high-resolution computerized tomography (HRCT).Objectives: To find out whether there are any abnormal HRCT features which can be attributed to asthma and their clinical correlates, and any differences of abnormal HRCT features between asthmatics and patients with chronic obstructive pulmonary disease (COPD). Methods: We performed (HRCT) scans to assess airway remodeling in 160 nonsmoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 21 publications
7
58
2
Order By: Relevance
“…However, they did not find the relationship between HRCT abnormalities and disease severities (14). In the study by Harmanci and colleagues (15), the incidence of bronchial wall thickening, bronchial dilatation, mucus impaction, and emphysema was reported as 67.9%, 9.3%, 1.8%, and 7.9% respectively, but they found that bronchial wall thickening, bronchial dilation, and mucus impaction were all correlated positively with asthma severity while negatively with forced expiratory volume in one second (FEV 1 ), which were further demonstrated by Park and Nakano (9,10). A study in China analyzed retrospectively the abnormalities of 28 asthma patients by HRCT, and the results showed a positive rate of 71.4%, of which bronchial wall thickening was detected in 15 cases (53.6%), while bronchial dilation was in 6 cases (21.4%), and mosaic pattern was in 3 cases (11.8%) (16).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, they did not find the relationship between HRCT abnormalities and disease severities (14). In the study by Harmanci and colleagues (15), the incidence of bronchial wall thickening, bronchial dilatation, mucus impaction, and emphysema was reported as 67.9%, 9.3%, 1.8%, and 7.9% respectively, but they found that bronchial wall thickening, bronchial dilation, and mucus impaction were all correlated positively with asthma severity while negatively with forced expiratory volume in one second (FEV 1 ), which were further demonstrated by Park and Nakano (9,10). A study in China analyzed retrospectively the abnormalities of 28 asthma patients by HRCT, and the results showed a positive rate of 71.4%, of which bronchial wall thickening was detected in 15 cases (53.6%), while bronchial dilation was in 6 cases (21.4%), and mosaic pattern was in 3 cases (11.8%) (16).…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, for a long time asthma is speculated to be more of a functional disease than a structural disease, which is distinct from chronic obstructive pulmonary disease (COPD), and airway structure abnormalities are indeed rarely found by chest film in asthmatics. However, in recent years, it has been recognized that airway remodeling is one of the important pathological abnormalities in patients with asthma and could lead to airway morphological changes, and an increasing number of studies have focused on the use of highresolution computed tomography (HRCT) to evaluate the airway structure changes (8)(9)(10)(11)(12)(13)(14)(15). It was reported that HRCT could be used to quantify static and dynamic changes in multiple independent airways as small as 1 mm (8), thus making it possible to study the subtle structure changes in the airways of asthma patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HARMANCI et al [43] demonstrated that bronchial wall thickening was more prominent with increased severity, decreased forced expiratory volume in one second (FEV1) values and the duration of asthma. The submucosa of asthmatic subjects contained more blood vessels; this also correlated with the severity of the disease [44].…”
Section: Is Remodelling Positively Correlated To Disease Severity?mentioning
confidence: 99%
“…High-resolution CT (HRCT) has recently gained increasing attention as an evaluation method of bronchial remodelling in asthma patients [1]. The efficiency of HRCT has been proven by numerous studies [2][3][4][5]. Optimisation of the radiation beam parameters enables identification of structures down to 100-200 mm in size and allows for evaluation of even the smallest bronchi (1.5-2 mm in diameter) [6].…”
Section: Discussionmentioning
confidence: 99%